ETHNO-RELIGIOUS COMPOSITION OF DERBENT IN THE VI–XIX CENTURIES - Magaramov, Sarafetdin Arifovic (History, Archeology and Ethnography of the Caucasus, 2020)
A number of scientific publications with the involvement of a wide range of sources and materials have been devoted to the study of ethno-demographic processes and religious composition of Derbent. However, this issue cannot be considered fully understood. The problem of the ethnic and religious composition of the city of Derbent in the medieval era and modern times has not been studied in a wider period with the involvement of archive material. A more complete picture of the ethno-confessional composition of Derbent can be reconstructed basing on data of a different nature of sources, including narrative sources and archival documents. The present paper aims to recreate the most complete and objective picture of the formation of the ethno-confessional composition of Derbent in the context of the events of foreign-policy of the region that took place from the 6th and up to the 19th century. The author proposes an upper chronological bound, based on the study of ethnographers M.-R.A. Ibragimov and M.M. Magomedkhanov on the ethno-confessional composition of Derbent in the end of the 19th – early 21st century, which is based on the population census. The article presents a reasoned author’s opinion regarding the ethnic composition of Derbent’s population in the Sasanian, Arabic, Seljuk and pre-Mongol periods. The study conducted shows that the ethno-religious processes of the medieval Derbent were significantly influenced by the events of the foreign political nature in the region: in different time periods, depending on the foreign policy situation, the specific gravity of one or another ethnic component changed, representatives of one or another confession dominated in the city. With the beginning of the Seljuk era, an active process of Turkification of Derbent’s population started, which continued over following periods. As a result, according to the household lists of 1886, ¾ of the city’s population were Turks (modern Azerbaijanis), the rest ¼ part was composed of the Jews, Armenians and Russians.
Keywords: Medieval Derbent; ethnic and confessional composition; Arab colonization; Turkic-speaking ethnic groups; Iranian-speaking groups; Shiism; family lists.